Combination therapy improves survival prognosis in anti-MDA5-antibody-positive dermatomyositis patients: a single-center retrospective study - Gao, Congcong; Wei, Gaohui; Li, Chaoying; Zhang, Chunyi; Wang, Chenqiong; Li, Ruxu; Shen, Kebing; Zheng, Zhaohui (Frontiers in Immunology, 2025)
BackgroundAnti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis (MDA5+DM) is associated with poor prognosis and high mortality, presenting significant challenges for treating this intractable disease. This study aimed to compare the efficacy and safety of calcineurin inhibitor monotherapy (CNI) versus combination therapy [CNI and tofacitinib (TOF) or cyclophosphamide (CTX)] as initial immunosuppressive regimens for MDA5+DM.MethodsIn this retrospective observational study, MDA5+DM patients from the First Affiliated Hospital of Zhengzhou University between August 2019 and June 2024 were included. Patients were categorized into three groups according to the different immunosuppressive regimens. One-year mortality and the potential risk factors for death was analyzed using the Kaplan-Meier survival analysis and Cox proportional hazards regression, respectively.ResultsA total of 152 patients were divided into CNI group(n=49, 32.2%), CNI+TOF group(n=52, 34.2%), and CNI+CTX group(n=51, 33.6%). The 1-year survival rate was significantly lower in the CNI group compared to in the combination therapy groups (logrank P = 0.032). However, the CNI+CTX group showed a higher overall infection rate compared to CNI and CNI+TOF group (51.0% vs 28.6% vs 32.7%, p=0.048). Multivariate analysis identified combination therapy and higher CD8+ T cells act as protective factors, whereas co-infection is a major predictor of mortality.ConclusionsIn our study, combination therapy may improve survival prognosis in MDA5+ DM patients. Nevertheless, vigilant monitoring for opportunistic infections during treatment is essential.